Deforestación en la RNN Nukak, el PNN Chiribiquete y sus alrededores entre 1990 y 2020, utilizando algoritmos de Machine Learning y sus cálculos de precisión (2010)
The present work is a study about the deforestation that occurred between 1990 and 2020 in an area of the Colombian Amazon rainforest; specically, the quadrant 6-59 of the Landsat satellite located between the departments of Caquetá, El Guaviare and Vaupés. This zone is highly important because it covers part of two National Natural Parks: Chiribiquete and Nukak. Supervised classications were performed in the study with ve Machine Learning algorithms, with their corresponding performance measures. Finally, the algorithm K Nearest Neighbor was the most efective, with an average precision of 93.3% and a Jaccard index of 0.932. With this algorithm it was calculated that in the previously mentioned interval of years, the rainforest coverage was reduced by an 5.57% in the study area, which equals to an area of 1,682.62 km2 and an annual deforestation rate of 52.22 km2/year. This concludes that in the surroundings of the National Parks Nukak and Chiribiquete the Amazon rainforest is being cut down and deforested in an alarming rate, despite the fact that the Natural Parks institution is constantly working on the task of reducing deforestation in the rainforest areas of Colombia. Additionally, in these 30 years is possible to observe deforestation in the western limit of the natural reserve Nukak, while the Park Chiribiquete stayed intact. The principal factors of the deforestation in this area are the expansion of the crops, both legal and illegal, and the construction of towns, roads and other infrastructures.--Taken from the Degree Document Format.